Relationship between tethered forces and the four swimming techniques performance - Morouco, P.; Keskinen, K. L.; Vilas-Boas, J. P.; Fernandes, R. J. (Journal of Applied Biomechanics, 2011)
The purpose of the current study was to identify the relationships between competitive performance and tether forces according to distance swam, in the four strokes, and to analyze if relative values of force production are better determinants of swimming performance than absolute values. The subjects (n = 32) performed a 30 s tethered swimming all-out effort. The competitive swimming velocities were obtained in the distances 50, 100 and 200 m using official chronometric values of competitions within 25 days after testing protocol. Mean force and velocity (50 m event) show significant correlations for front crawl (r = .92, p < .01), backstroke (r = .81, p < .05), breaststroke (r = .94, p < .01) and butterfly (r = .92, p < .01). The data suggests that absolute values of force production are more associated to competitive performance than relative values (normalized to body mass). Tethered swimming test seems to be a reliable protocol to evaluate the swimmer stroking force production and a helpful estimator of competitive performance in short distance competitive events.